2012
DOI: 10.1371/journal.pone.0038630
|View full text |Cite
|
Sign up to set email alerts
|

Immune Responses to Plague Infection in Wild Rattus rattus, in Madagascar: A Role in Foci Persistence?

Abstract: Background Plague is endemic within the central highlands of Madagascar, where its main reservoir is the black rat, Rattus rattus . Typically this species is considered susceptible to plague, rapidly dying after infection inducing the spread of infected fleas and, therefore, dissemination of the disease to humans. However, persistence of transmission foci in the same area from year to year, supposes mechanisms of maintenance among which rat immune responses could play a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…In a subsequent series of experiments examining infection on the basis of Y. pestis isolation from rats' blood, resistance was shown to prevent the onset of infection rather than merely reduce the severity of symptoms among infected rats (46). The existence of such innate resistance has been confirmed more recently by experimental assays in R. rattus from plague-endemic areas that do not experience infection, disease, or seroconversion after Y. pestis exposure (27,64,71).…”
Section: Methodsmentioning
confidence: 87%
See 3 more Smart Citations
“…In a subsequent series of experiments examining infection on the basis of Y. pestis isolation from rats' blood, resistance was shown to prevent the onset of infection rather than merely reduce the severity of symptoms among infected rats (46). The existence of such innate resistance has been confirmed more recently by experimental assays in R. rattus from plague-endemic areas that do not experience infection, disease, or seroconversion after Y. pestis exposure (27,64,71).…”
Section: Methodsmentioning
confidence: 87%
“…Such conditions are met in the urban plague ecology of colonial India and supported the persistence of polymorphisms in our model in agreement with the findings of historical investigations (42). More recently, field studies have shown similar local persistence of resistance polymorphisms among R. rattus inhabiting plague foci in Madagascar, Asia, and Hawaii (27,31,64,71,94).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…128 However, the immune response to infection may differ even for the same species of rat from the same endemic focus. 130 Genetic structure analysis of R. rattus populations in a rural plague focus showed that ecology may support selection for resistance to plague. 131 Sylvatic plague is much less frequent in the country.…”
Section: Biological Factorsmentioning
confidence: 99%